ChemInform Abstract: Diversity‐Oriented Synthesis of Fused‐Imidazole Derivatives via Groebke—Blackburn—Bienayme Reaction: A Review. Issue 12 (March 2015) - Devi, Nisha; Rawal, Ravindra K.; Singh, Virender
Abstract Review: [106 refs.